Analysis of Zakat as an Alternative Fiscal Instrument in Supporting Economic Development in Indonesia - Judijanto, Loso; Ilhamiwati, Mega; Rosid, Abdul; Muhammadong, Muhammadong (Westscience Press, 2024)
This study explores the potential of zakat as an alternative fiscal instrument in supporting economic development in Indonesia. Zakat, a mandatory charitable contribution in Islam, has the ability to address poverty, reduce income inequality, and contribute to economic growth. Using a quantitative approach, data were collected from 80 respondents, including zakat payers, recipients, and administrators, through a Likert-scale survey. The data were analyzed using SPSS version 26 to evaluate the impact of zakat distribution efficiency and utilization on poverty reduction and economic development. The results demonstrate that both zakat distribution efficiency and utilization significantly contribute to poverty reduction and economic development, supporting the hypothesis that zakat can play a crucial role as a fiscal tool. The study's findings suggest that improving zakat management practices and aligning zakat utilization with long-term development goals could enhance its impact on Indonesia's economic growth.